Bridging the Gap in Pension Participation: How Much Can Universal Tax-Deferred Pension Coverage Hope to Achieve? - Nadia Karamcheva; Geoffrey Sanzenbacher (Institute for the Study of Labor (IZA), 2013)
In light of the declining pension coverage of low-income workers, policy makers have discussed requiring all employers to offer individual retirement accounts, similar to defined contribution plans. How likely to participate are workers who currently do not have access to a pension plan? We address this question by using plausibly exogenous variation in pension-plan availability to estimate the determinants of participation in a standard selection on unobservables model. We find that currently uncovered low-income workers are fairly likely to participate in a newly offered plan, yet they are much less likely to do so than currently covered workers.
Keywords: J08; J26; J32; 330; private pensions; participation; self-selection; policy effects